2022
DOI: 10.3390/agriculture12030385
|View full text |Cite
|
Sign up to set email alerts
|

Feature Wavelength Selection Based on the Combination of Image and Spectrum for Aflatoxin B1 Concentration Classification in Single Maize Kernels

Abstract: Aflatoxin B1 (AFB1) is a very strong carcinogen, maize kernels are easily infected by this toxin during storage. Rapid and accurate identification of AFB1 is of great significance to ensure food safety. In this study, a novel method for classification of AFB1 in single maize kernels was developed. Four groups of maize kernel samples with different AFB1 concentrations (10, 20, 50, and 100 ppb) were prepared by artificial inoculation of toxin. In addition, one group of maize kernel samples without AFB1 were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Image processing techniques developed from machine learning is also gaining attention due to their nondestructive application for mycotoxins monitoring. Such has been applied for AFB1 in grains and feed commodities [16][17][18][19]. Machine learning methods, however, have limitations in terms of data volume, noises from the sensor, and calibration errors, besides being unable to ascertain types of mycotoxins produced.…”
Section: Mycotoxins and Their Detections 21 Current State Detection F...mentioning
confidence: 99%
“…Image processing techniques developed from machine learning is also gaining attention due to their nondestructive application for mycotoxins monitoring. Such has been applied for AFB1 in grains and feed commodities [16][17][18][19]. Machine learning methods, however, have limitations in terms of data volume, noises from the sensor, and calibration errors, besides being unable to ascertain types of mycotoxins produced.…”
Section: Mycotoxins and Their Detections 21 Current State Detection F...mentioning
confidence: 99%
“…This contains many methods for data analysis and machine learning. The information required to create a sound and sustainable plan to address various major issues in oilseed cropping systems might be found in yield and quality level.In [40],author's have concluded that maize is one of the most significant crops in the world. The fungus mostly infects this during storage.…”
Section: Futurementioning
confidence: 99%
“…Sometimes a single WV optimization method fails to meet the requirements of the analysis, and a combination of methods is required [ 23 , 24 , 25 ]. BIPLS, CARS, and GSA are the most typical methods used in spectral region optimization, wavelength selection, and intelligent optimization, respectively, and are widely used in wavelength selection for high-dimensional spectral data [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%